AVALIAÇÃO IMUNOHISTOQUÍMICA DE FIBRONECTINA TECIDUAL EM PULMÃO DE EQUINOS COM OBSTRUÇÃO RECORRENTE DAS VIAS AÉREAS (ORVA) - WERNER, LAÍS CRISTINE (2016)
Recurrent airway obstruction is a lower respiratory pathology associated with resting dyspnea and exercise intolerance. It presents a clinical and pathophysiological condition very similar to human asthma and, within the observed changes, the remodeling of the extracellular matrix and consequent remodeling of the airways is a critical point of the affection. For the analysis of fibronectin distribution within this remodeling process, tissue fibronectin was quantified in lung from animals affected by recurrent airway obstruction and control group, immunohistochemistry was used for this purpose. Image editing program (Image J®) was also used to enable the measurement of the 20 photographed areas of each slide / animal. The correlation of the obtained areas: total, white, tissue and brown in the lung tissue through the calculation of volume fraction (FV) did not show a significant difference in the area´s correlations of the observed groups, suggesting that this glycoprotein, despite its important function in the development and reestablishment post-lung injury, may in this stage of exacerbation of the disease, not play an important role. Considering the staging of this obstruction of the studied animals and that different sources of fibronectin vary in their functions and times of action in the lung in the development phases and during injuries.